The Chevron Effect and Analysis of Chevron Beams—A Paradigm Shift - Fortney, Patrick J.; Thornton, William A. (Engineering Journal, 2017)
Beam designers and connection designers have a different standard of care in the analysis of beams in inverted V- and V-type braced frames subjected to lateral loads. When the summation of the vertical components of the brace forces is nonzero, (1) beam designers evaluate required beam shear and moment, treating the unbalanced vertical load as a concentrated force acting at the work point of the braces while ignoring any local effects resulting from the brace connection geometry, and (2) the connection designer evaluates the required beam shear based only on the moment acting at the gusset-to-beam interface(s). Thus, the beam designer considers beam span and work point location ignoring the local effect of the connection, and the connection designer considers the local effects of the connection while ignoring beam span and the location of the work point. This paper proposes a new method for evaluating required beam shear and moment that includes consideration of beam span, location of work point, and the local effects of the connection—a method that can be used by both the beam designer and the connection designer. Discussion is also provided to illustrate how this proposed method can be used to evaluate whether or not the local connection effect dominates the global effect. It is shown that the magnitude of the unbalanced vertical load influences the impact of the local connection effects; when the summation of the vertical brace force components is zero or relatively small, the local connection effects dominate the global effect. Conversely, when the unbalanced vertical load is relatively large, the global effects dominate; in this case, including the local connection effects will predict a smaller required beam moment possibly allowing for lighter beams.